1993
DOI: 10.1111/j.1432-1033.1993.tb18447.x
|View full text |Cite
|
Sign up to set email alerts
|

The actin/actin interactions involving the N‐terminus of the DNase‐I‐binding loop are crucial for stabilization of the actin filament

Abstract: Actin can be specifically cleaved between residues 42 and 43 with a novel protease from Escherichia coli A2 strain (ECP) [Khaitlina, S. Y., Collins, J. H., Kuznetsova, I. M., Pershina, V. P., Synakevich, I. G., Turoverov, K. K. & Usmanova, A. M. (1991) FEBS Lett. 279, 49-51]. The resulting C-terminal and N-terminal fragments remained associated to one another in the presence of either Ca" or Mg". The protease-treated actin was, however, neither able to spontaneously assemble into filaments nor to copolymerize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 44 publications
8
89
0
Order By: Relevance
“…The cleavage products were analysed by SDS-PAGE [7]. Integrity of the cleaved molecules with which the C-terminal core and N-terminal 8 kDa fragments remain associated as long as the cleaved actin contains a tightly bound cation [2,8] was proved by the presence of both fragments in the samples obtained after a cycle of polymerization-depolymerization (Fig. 1).…”
Section: Proteolytic Digestionmentioning
confidence: 99%
“…The cleavage products were analysed by SDS-PAGE [7]. Integrity of the cleaved molecules with which the C-terminal core and N-terminal 8 kDa fragments remain associated as long as the cleaved actin contains a tightly bound cation [2,8] was proved by the presence of both fragments in the samples obtained after a cycle of polymerization-depolymerization (Fig. 1).…”
Section: Proteolytic Digestionmentioning
confidence: 99%
“…Several studies have shown that proteolytic cleavage (15,16) of the DNase I-binding loop or chemical modification of neighboring residues Lys-61 (17)(18)(19) and Tyr-69 (20) reduce actin's affinity for DNase I and inhibit polymerization, which is reversed by phalloidin. More directly relevant to this article, chemical modification of Tyr-53 by reaction with diazonium tetrazole also blocks polymerization (21), which is not reversed by phalloidin (20).…”
Section: Discussionmentioning
confidence: 99%
“…The fungal toxin phalloidin and actinbinding protein cofilin can rescue via different mechanisms the polymerization of actins whose self-assembly was impaired by mutations, limited proteolysis, or chemical modifications (23)(24)(25)(26). Therefore, we used these two actin-interacting partners to test the rescue of filament assembly for ACD cross-linked actin.…”
Section: Phalloidin and Cofilin Independently Rescue The Polymerizatimentioning
confidence: 99%